Brimonidine for Prevention of Intraocular Pressure Elevation after YAG-Posterior Capsulotomy: Doi: 10.36351/pjo.v36i2.1006 - Niazi, Muhammad Khizar; Rauf, Ali; Nadeem, Yasser (Pakistan Journal of Ophthalmology, 2020)
Purpose: To see the efficacy of Brimonidine 0.2% in controlling intraocular pressure (IOP) elevations after YAG-posterior capsulotomy. Study Design: Quasi Experimental study. Place and Duration of Study: Combined Military Hospital, Lahore from February to December 2019. Material and Methods: Eighty four pseudophakic eyes with Posterior capsular opacities were included in the study. Exclusion criteria were; complications during surgery and in postoperative period. Cases with any other ocular disease or history of ophthalmic surgeries prior to Nd: YAG laser posterior capsulotomy was also excluded from the study. Prior to YAG capsulotomy patients were either administered Brimonidine 0.2% or were not given any IOP lowering drug after noting a rise in Intra-ocular pressure. Eyes received either one drop of Brimonidine 0.2% per day starting one hour after the laser procedure or no treatment after laser therapy. Intraocular pressure was measured one hour and three days after laser therapy in both the groups. Result: Mean IOP of 84 eyes was 14.43mm of Hg. One hour after the procedure, 52 patients had a rise in IOP. Mean IOP-hike was 8.76 mm of Hg. 26 patients were administered Brimonidine drops immediately while rest were left untreated and observed. On the third day of laser therapy, only one patient had an increased IOP in the treated group while 18 patients in the un-treated group had a higher than normal IOP. After 3rd day, all patients were treated for the raised IOP. Conclusion: Once daily dose of Brimonidine 0.2% is effective in maintaining a lower IOP after YAG capsulotomy.